IMPLEMENTASI NILAI PENDIDIKAN PANCASILA DI ERA DIGITAL PADA SISWA SDN 101964 JAHARUN A KECAMATAN GALANG - Cindi Safitra Saragih (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
Moral degradation refers to a condition where there is a decline in morality, where individuals or groups violate the norms and values that apply in society. A person's morality can be seen from the extent to which the individual's actions respect and comply with moral values in society. Therefore, elementary school students must be able to understand the moral values expected by society without being influenced by external factors. Elementary school students in the digital age, have a strong interest in digital/technology growing up with easy access to technology. Their lives are drastically different compared to previous generations due to growing up and developing in the era of century change. Pancasila, as a philosophy of life, expects the morals of Pancasila to be the morals of state life. This means that the state and its organizers are expected to respect and adhere to moral principles or political ethics. As a consequence, the state is obliged to practice and submit to these morals. Morals become the norms of state action and policy, so they need to be regulated in legislation. One of the causes of moral degradation is the influence of globalization in Indonesia. Although globalization can improve people's morals, it must be balanced with the implementation of good and effective Pancasila education values, in order to realize good Pancasila students.